PELATIHAN PEMBUATAN PUPUK ORGANIK CAIR DARI URINE KAMBING DI DESA TANJUNG SARI, KABUPATEN OKU - Nurlaili, Nurlaili; Pusvita, Ema; Gribaldi, Gribaldi; Asroh, Ardi; Novriani, Novriani; Danial, Ekawati; Yulhasmir, Yulhasmir; Diana, Susanti; Dewi, Nurmala; Sakalena, Firnawati; Fatmanurshanti, Dora; Lastinawati, Endang; Rosmawati, Henny; Ogari, Putri Ayu; Lestari, Windi (Penerbit Widina, Widina Media Utama, 2026)
This Community Service (PkM) activity was carried out in Tanjung Sari Village, Pengandonan District, Ogan Komering Ulu Regency (OKU), to improve the knowledge and skills of farmers/breeders in utilizing goat urine waste as raw material for liquid organic fertilizer (POC). The main problem of the community is the dependence on chemical fertilizers and the lack of optimal use of livestock waste that has the potential to pollute the environment. The implementation method is carried out through counseling, training, and demonstrations of making POC using local ingredients (goat urine, ginger-turmeric-galangal rhizomes, EM4, dolomite, shrimp paste, and molasses). POC is fermented for two weeks and applied to corn and vegetable crops at a dose of 200 ml/L of water. Field observations showed that plants that were given POC had greener leaves, stronger stems, and more uniform growth compared to controls without POC. This activity improves farmers' practical skills in producing organic fertilizers independently and encourages productive livestock waste management. Thus, this PkM contributes to increasing crop productivity and strengthening sustainable agricultural practices in Tanjung Sari Village.ABSTRAKKegiatan Pengabdian kepada Masyarakat (PkM) ini dilaksanakan di Desa Tanjung Sari, Kecamatan Pengandonan, Kabupaten Ogan Komering Ulu (OKU), untuk meningkatkan pengetahuan dan keterampilan petani/peternak dalam memanfaatkan limbah urine kambing sebagai bahan baku pupuk organik cair (POC). Permasalahan utama masyarakat adalah ketergantungan pada pupuk kimia dan belum optimalnya pemanfaatan limbah ternak yang berpotensi mencemari lingkungan. Metode pelaksanaan dilakukan melalui penyuluhan, pelatihan, dan demonstrasi pembuatan POC menggunakan bahan lokal (urine kambing, rimpang jahe-kunyit-lengkuas, EM4, dolomit, terasi, dan molase). POC difermentasi selama dua minggu dan diaplikasikan pada tanaman jagung dan sayuran dengan dosis 200 ml/L air. Hasil pengamatan lapangan menunjukkan tanaman yang diberi POC memiliki daun lebih hijau, batang lebih kuat, serta pertumbuhan lebih seragam dibandingkan kontrol tanpa POC. Kegiatan ini meningkatkan keterampilan praktis petani dalam memproduksi pupuk organik secara mandiri serta mendorong pengelolaan limbah ternak yang produktif. Dengan demikian, PkM ini berkontribusi pada peningkatan produktivitas tanaman dan penguatan praktik pertanian berkelanjutan di Desa Tanjung Sari.